Addressing Learning Gaps in Earth and Life Science through Strategic Intervention Material - Edna M. Padre; Mauren D. Bitancur (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Amidst the evolving landscape of science education, addressing persistent learning gaps requires the integration of targeted pedagogical tools tailored to diverse learner needs. Hence, this study investigated the effectiveness of a developed Strategic Intervention Material (SIM) in enhancing the academic performance of Grade 11 students in Earth and Life Science. Employing a quasi-experimental pretest-posttest design, the study involved 60 learners, randomly assigned into Control (N=30) and Experimental (N=30) groups. Findings revealed that both groups initially exhibited a lower average proficiency level, with pre-test mean scores of 7.23 and 8.23, respectively, highlighting significant learning gaps. Following the intervention, the Experimental group’s performance improved substantially to a superior level, achieving a post-test mean of 21.23 (MPS = 84.93), whereas the Control group showed minimal gains (Mean = 8.13; MPS = 32.53). Furthermore, there is a significant difference between the raw scores of the respondents in the pre-test and post-test (p=0.000). The results demonstrate that the SIM effectively addressed least-mastered competencies and bridged learning gaps in Earth and Life Science more effectively than traditional approach. This study likewise underscores the value of localized intervention materials in fostering academic resiliency and mastery among secondary learners. Ultimately, these results suggest that educational policymakers should institutionalize the development of localized SIMs and integrate them into formal remedial programs to provide a scalable solution for addressing achievement gaps in science.